Analysis of chronic patient management with communication SBAR and interprofessional collaboration (IPC) - Mei Astuti, Andriani; Bala Krishnan, Arvind; Probowati, Rovica; Buyu Prakoso, Adi; Firdaus, Insanul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The occurrence of chronic diseases is a predominant challenge in global public health. Chronic diseases have a high incidence; according to the 2021 study conducted by the Global Burden of Disease, chronic diseases such as hypertension and diabetes are included in the top five death risks in the world and are responsible for approximately 20% of global deaths. SBAR communication technique is the prioritized indicator for effective communication quality in patient safety goal (IPSG 2). Patient safety highly depends on the medical team’s action in decreasing unwanted incidence, which can be prevented by increasing effective communication through socializing SBAR communication. The purpose of this study was to analyze the effect of implementing SBAR communication in interprofessional collaboration (IPC) between doctors and nurses on patient safety. The research used a quasi-experimental method with a one-group pretest-posttest design. The respondents were 35 nurses and 35 doctor specialists according to the inclusion criteria with purposive sampling. The research instruments were SBAR communication questionnaires, with a validity value of CVI=0.87 and a reliability value of Cronbach’s Alpha=0.62. Data was analyzed using the Wilcoxon Test. The results showed a significant difference in pre-post SBAR implementation scores between doctors and nurses (p=0.04; p<0.05). The research results showed that the Mean Rank was 18.00 for both doctor specialists and nurses, indicating that socializing SBAR communication could significantly change the mean rank value.